1997
DOI: 10.1021/jf970077f
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Amino Acid Profile, Fatty Acid Composition, and Mineral Content of Peanut Seeds Hydroponically Grown at Elevated CO2 Levels

Abstract: Peanut plants (Arachis hypogaea L. cv. Georgia Red) were grown hydroponically using a recirculating nutrient film technique. The effect of CO2 enrichment on nutritive composition of hydroponic peanut seeds was examined at two elevated CO2 levels (700 and 1400 ppm) that simulate potential conditions in National Aeronautics and Space Administration (NASA) Controlled Ecological Life-Support Systems (CELSS) and compared to ambient CO2 condition in hydroponics (the control). Plants were harvested at 97 days after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
14
2
Order By: Relevance
“…Bauhinia grains also contained substantial amounts of zinc (6 mg/100 g) and iron (3 mg/100 g) when compared to FAO/ WHO standards. The mineral composition of Bauhinia appeared similar to oilseeds such as marama bean (Amonsou et al 2011), peanuts (Wu et al 1997) and other Bauhinia species such as the B. monandra (Anhwange et al 2005). …”
Section: Chemical Composition Of Bauhinia Grainsmentioning
confidence: 84%
“…Bauhinia grains also contained substantial amounts of zinc (6 mg/100 g) and iron (3 mg/100 g) when compared to FAO/ WHO standards. The mineral composition of Bauhinia appeared similar to oilseeds such as marama bean (Amonsou et al 2011), peanuts (Wu et al 1997) and other Bauhinia species such as the B. monandra (Anhwange et al 2005). …”
Section: Chemical Composition Of Bauhinia Grainsmentioning
confidence: 84%
“…Different effects of elevated CO 2 on oil yield in oil crops have been reported. No change in oil content could be observed in peanut ( Arachis hypogaea ) (Wu et al ., 1997) and oil seed rape (Frick et al ., 1994). CO 2 enrichment stimulated the seed yield of soybean ( Glycine max ), but the effects on seed oil content were variable, with differences among cultivars (Heagle et al ., 1998; Ziska et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Some elevated CO 2 studies reported decreased N concentration in soybean seed (Rogers et al 1984) while others reported no effect (Allen et al 1988). There were no reported effects of elevated CO 2 on nutrient composition and mineral nutrients in peanut (Arachis hypogaea L.) seeds (Wu et al 1997). There was no effect of parental plant growth at elevated CO 2 on subsequent seedling emergence of soybean (Rogers et al 1980) and wheat (Triticum aestivum L; .…”
Section: Introductionmentioning
confidence: 98%
“…2003). There were no reported effects of elevated CO 2 on nutrient composition and mineral nutrients in peanut ( Arachis hypogaea L.) seeds (Wu et al. 1997).…”
Section: Introductionmentioning
confidence: 99%